Social Capital and Participation in Moslem Organizations - Hawari, Muhammad Irsyad; Hasanah, Alfiah; Adam, Asep Muhammad (Al-Tijary, 2022)
Indonesia, as the country with the largest Muslim population in the world, has numerous Muslim organizations that play a significant role in the social and economic lives of its people. This study aims to address the impact of participation in Moslem organizations on social capital in a setting of a country with the biggest Moslem population in the world. A survey of members and non-members of Moslem organization Muhammadiyah in Bandar Lampung City was conducted. The quantitative approach is used to display the data on the degree to which Muhammadiyah Moslem organizations' involvement has impacted the social capital index. The data analysis technique used is propensity score matching (PSM) analysis. The findings demonstrated that members of Muhammadiyah and non-Muhammadiyah had different social capital indices. Additionally, a person's involvement in Muslim groups significantly affects social capital. It suggests that Moslem organizations are not only present to provide religious understanding for their members but also capable of providing added value for them, that is, the addition of social capital for each member. Based on the study, participation in Moslem organizations like Muhammadiyah significantly enhances social capital among members, suggesting that these organizations provide not only religious guidance but also valuable social benefits.